A growing disparity in earnings disclosure mechanisms: The rise of concurrently released earnings announcements and 10-Ks - Arif, Salman; Marshall, Nathan T.; Schroeder, Joseph H.; Yohn, Teri Lombardi (Journal of Accounting and Economics, 2019)
We document a growing disparity in earnings disclosure mechanisms. Firms are increasingly disclosing earnings announcements (EA) concurrently with the 10-K filing instead of first issuing a ‘stand-alone’ EA. Firm adoption of concurrent EA/10-Ks is associated with lower investor sophistication, greater impediments to producing timely and reliable earnings information, and greater industry-level concurrent reporting. Concurrent EA/10-Ks differ from stand-alone EAs in that investors anticipate more information in the EA, disclosures are preempted by industry peer EAs, the market reaction is muted even when controlling for EA timing, and post-earnings-announcement drift is greater.